Marcelo Engel Bronosky - O Jornalista da Resistência - Maluly, Luciano Victor Barros (Universidade de São Paulo | Escola de Comunicações e Artes, 2016)
He is considered a “fighter“ in the defense of the Graduate Journalism Courses, being one of the Post-Graduate Course Stricto Sensu founders in Journalism at University of Ponta Grossa, in Paraná (Brazil), where he has been working since his graduation. Polemic debates around themes as: Journalism of Resistance, Writing Manuals, Newspaper-Lab, the quality of Journalism courses and Science dissemination integrate the studies of the professor and researcher Marcelo Engel Brononsky, PhD in Communication Sciences (UNISINOS) and coordinator of the Research Group in Logic of Production and Consumption of Journalism.